Correlates of new psychoactive substance use among a self‐selected sample of nightclub attendees in the United States. Issue 5 (15th July 2016) - Palamar, Joseph J.; Barratt, Monica J.; Ferris, Jason A.; Winstock, Adam R.
Abstract : Background and Objectives: Although new psychoactive substances (NPS) continue to emerge at a rapid rate, US national surveys only measure the use of non‐specific categories of NPS and are not designed to access high‐risk populations. In this paper we report lifetime use of specific NPS (of 58) and examine correlates of use among a high‐risk population: nightlife attendees. Methods: The self‐selected sample from the Global Drug Survey (2013) consisted of 2, 282 respondents in the US, aged 16–60 years, who reported nightclub attendance in the last year. Multivariable logistic regression models determined unique predictors of lifetime use. Results: Lifetime use of a wide range of NPS was reported (any NPS; 46.4%), including synthetic cannabinoids (24.8%), tryptamines (eg, 4‐AcO‐DMT, 23.0%), psychedelic phenethylamines (eg, 2C‐B, 25I‐NBOMe; 21.7%), euphoric stimulants (eg, BenzoFury; 16.2%), and synthetic cathinones (eg, methylone; 10.5%). Females (AOR = 0.49 [.41, .60]) and older respondents (age 22–60; AOR = .73 [.59, .89]) were at lower odds of reporting any lifetime NPS use. Frequent nightclub attendance was associated with increased odds of reporting lifetime NPS use overall (eg, weekly compared with less than once a month, AOR = 2.33 [1.70, 3.19]), but not specifically with synthetic cannabinoid use. Discussion and Conclusions: Among a self‐selected sample of nightclub attendees, a large range of novel substances were reported, and young attendees, males, and those who attended more frequently were at increased odds of reporting use. Scientific Significance: Harm reduction initiatives are needed to reduce risk of harm in this population, where environmental characteristics may augment risks associated with consuming lesser‐known psychoactive substances. (Am J Addict 2016;25:400–407)